Integrated mapping of the earthquake-induced liquefaction in Wates Groundwater Basin, Kulon Progo for land use planning consideration: A preliminary study - Ilham, Muhamad; Putra, Doni Prakasa Eka (2022)
Since the development of New Yogyakarta International Airport (NYIA), land use planning and development in Wates Groundwater Basin, Kulon Progo, Indonesia, becoming more crucial. A regional-scaled study led by Buana et al. (2019) pointed out the area as moderate-high susceptibility to liquefaction. This study provides updated land-use conditions and a detailed liquefaction susceptibility map using Geographic Information System and Multi-Criteria Analysis (GIS-MCA) from the previous research data by Maulana (2017). The result shows that the south and east part of the basin is classified as very high susceptibility to liquefaction while the other part is low to moderate susceptibility class. This preliminary study suggests the best recommendation for geophysics and Standard Penetration Test (SPT) data acquisition in further analysis.